2017
DOI: 10.1038/pr.2017.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic hypothermia on white matter injury from murine neonatal hypoxia–ischemia

Abstract: BackgroundTherapeutic hypothermia (TH) is the standard of care for neonates with hypoxic-ischemic encephalopathy but is not fully protective in the clinical setting. Hypoxia-ischemia (HI) may cause white matter injury (WMI), leading to neurological and cognitive dysfunction.MethodsP9 mice were subjected to HI as previously described. Pups underwent 3.5 hours of systemic hypothermia or normothermia. Cresyl violet and Perl’s iron stain for histopathological scoring of brain sections was completed blindly on all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Hypothermia treatment significantly reduced the ischemia-induced reactive astrocytosis and microgliosis in the hippocampal CA1 region, but GFAP and Iba-1 immunoreactivity was significantly increased in the hippocampal CA1 region compared to the CTL group. This result is consistent with a previous study demonstrating that therapeutic hypothermia significantly decreased the intensity of GFAP and Iba-1 staining in hippocampal CA2/CA3 regions in correlation with a reduced injury score [43]. Mild hypothermia in global cerebral ischemia has been shown to decrease microglial activation and translocation of nuclear factor-kappa B [44].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hypothermia treatment significantly reduced the ischemia-induced reactive astrocytosis and microgliosis in the hippocampal CA1 region, but GFAP and Iba-1 immunoreactivity was significantly increased in the hippocampal CA1 region compared to the CTL group. This result is consistent with a previous study demonstrating that therapeutic hypothermia significantly decreased the intensity of GFAP and Iba-1 staining in hippocampal CA2/CA3 regions in correlation with a reduced injury score [43]. Mild hypothermia in global cerebral ischemia has been shown to decrease microglial activation and translocation of nuclear factor-kappa B [44].…”
Section: Discussionsupporting
confidence: 93%
“…This result suggests that cuprizone facilitates the demyelination induced by ischemia, and that hypothermia attenuates the demyelination induced by ischemia and/or cuprizone. Furthermore, MBP staining also suggests that hypothermia increases white matter integrity in mice after inducing the hypoxia-ischemia model [43] and after middle cerebral artery occlusion [56].…”
Section: Discussionmentioning
confidence: 97%
“…For example, perinatal asphyxia without encephalopathy leads to a reduction in IQ compared with healthy peers, and mild, moderate and severe encephalopathy results in increasing severity of long-term adverse outcomes. Hypothermia is reported to have a marked neuroprotective effect in a recently described preclinical model of mild encephalopathy, where the predominant injury was in the white matter 11. Preclinical studies also report that brain cooling in the absence of perinatal asphyxia may increase apoptosis 12…”
Section: Discussionmentioning
confidence: 99%
“…There are concerns with such practices, as the cessation of cooling therapy prior to 24 hours following an apparent clinical recovery may be associated with residual brain injury and adverse outcomes 2. Furthermore, cooling therapy in the absence of NE may induce apoptosis 3. In contrast to the systematic review of cooling in mild NE reported by Conway et al , our review includes additional published studies, as well as raw data provided by the study authors 4…”
Section: Introductionmentioning
confidence: 99%